29.4: Flexible AMOLED Display with Integrated Gate Driver Operating at Operation Speed Compatible with 4k2k. Issue 1 (June 2015) - Steudel, Soeren; Cobb, Brian; Nag, Manoj; Obata, Koji; Murata, Mitsuhiro; Myny, Kris; Schols, Sarah; Vicca, Peter; Tung Huei, Ke; Smout, Steve; Willegems, Myriam; Ameys, Marc; et al.
Abstract : We present a QVGA (320x240 with 3 sub‐pixel) top‐emitting AMOLED display with 250ppi resolution using a self‐aligned (SA) IGZO TFT backplane on polyimide‐foil with full barrier. The back plane process flow is based on a 7 layer photolithography process. The aperture ratio of the top‐emitting OLEDs is approx. 80%. An integrated gate driver is shown that can be driven at operation speed equivalent to a 4k2k display at 100Hz.